Bacterial community associated with traps of the carnivorous plants Utricularia hydrocarpa and Genlisea filiformis - Caravieri, Fernanda A.; Ferreira, Almir J.; Ferreira, Anderson; Clivati, Debora; Miranda, Vitor Fernandes O. de [UNESP]; Araujo, Welington L. (Elsevier B.V., 2014)
The species of bacteria associated with the traps of the carnivorous plants Utricularia hydrocarpa Vahl and Genlisea filiformis A. St.-Hil. were identified by analysing 16S rRNA gene libraries. We observed larger bacterial diversity inside the traps of U. hydrocarpa than in G. filiformis. The Clostridium genus (Firmicutes) was the dominant group in G. filiformis,while Aeromonas (gamma-Proteobacteria) and Acidobacterium(Acidobacteria) were the dominant genera in U. hydrocarpa. In general, the microbial community observed in these carnivorous plants was composed of Firmicutes (46.8%), Proteobacteria (33.9%), Acidobacteria (9.3%), Actinobacteria (4.4%), Bacteroidetes (0.8%), Chloroflexi (0.4%), Gemmatimonadetes (0.4%), Cyanobacteria (0.4%), Chlamydiae (0.4%) and Tenericutes (0.4%). Only 1.2% of the observed operational taxonomic units (OTU0.03) were shared by U. hydrocarpa and G. filiformis. The present study describes the dominant bacterial species associated with the traps of the carnivorous plant G. filiformis and U. hydrocarpa and briefly discusses the possible role of bacteria in plant prey utilisation. (c) 2014 Elsevier B.V. All rights reserved.
Keywords: microbial ecology; Prey digestion; Microbial community; Habitat specificity; Lentibulariaceae